EVALUASI USABILITY APLIKASI WHATSAPP MENGGUNAKAN METODE SYSTEM USABILITY SCALE (SUS) - M.Rizky Ramadhan; Arif Sandika; Abiyyu Adzin; M. Khalil Gibran (EDUTECH : Jurnal Inovasi Pendidikan Berbantuan Teknologi, 2026)
ABSTRACT WhatsApp has evolved from a platform for personal conversations into a communication space used for group coordination, document sharing, and information dissemination across various daily activities. Its widespread use does not necessarily reflect a uniform user experience; therefore, evaluating its usability is necessary to understand users’ level of acceptance when interacting with the available features. This study evaluates the usability of WhatsApp from the perspectives of active users by employing the System Usability Scale (SUS). Data were collected online through an SUS questionnaire administered to 33 respondents selected purposively based on their experience using WhatsApp as a daily communication medium. Each participant’s responses were converted according to the SUS scoring procedure and calculated to obtain scores ranging from 0 to 100. The mean score reached 74.39, placing WhatsApp in the acceptable category. These findings indicate that respondents generally perceived WhatsApp as a relatively easy-to-use communication application, although variations in individual user experiences may still occur. This study provides empirical evidence regarding the usability acceptance of WhatsApp among active users and may serve as a basis for further evaluations focusing on navigation, interface consistency, and the use of specific features in greater depth. ABSTRAK WhatsApp telah berkembang dari sarana percakapan personal menjadi ruang komunikasi yang digunakan untuk koordinasi kelompok, pertukaran dokumen, serta penyampaian informasi dalam berbagai aktivitas sehari-hari. Luasnya penggunaan aplikasi tersebut belum selalu menggambarkan pengalaman pengguna yang seragam, sehingga evaluasi terhadap aspek usability diperlukan untuk memahami tingkat penerimaan pengguna dalam berinteraksi dengan fitur yang tersedia. Penelitian ini mengevaluasi usability WhatsApp melalui persepsi pengguna aktif dengan memanfaatkan System Usability Scale (SUS). Data dihimpun secara daring melalui kuesioner SUS dari 33 responden yang dipilih secara purposive berdasarkan pengalaman menggunakan WhatsApp sebagai media komunikasi sehari-hari. Respons setiap partisipan dikonversi mengikuti aturan penilaian SUS, kemudian dihitung untuk memperoleh skor pada rentang 0–100. Nilai rata-rata yang diperoleh mencapai 74,39 dan berada pada kategori acceptable. Temuan tersebut menunjukkan bahwa WhatsApp secara umum diterima responden sebagai aplikasi komunikasi yang relatif mudah digunakan, meskipun variasi pengalaman antarindividu tetap memungkinkan terjadi. Studi ini menyediakan gambaran empiris mengenai penerimaan usability WhatsApp pada pengguna aktif serta dapat menjadi pijakan bagi evaluasi lanjutan yang menelaah navigasi, konsistensi antarmuka, dan penggunaan fitur tertentu secara lebih mendalam.